Juegos tradicionales en el aprovechamiento del tiempo libre de estudiantes de bachillerato. - Tenezaca Guaman, Jonathan Estuardo (2023)
The following research work makes an analysis of the traditional games in the use of leisure time of 70 students of second year of high school classes A(20), B(24), C(26) of the Educational Unit Nicanor Larrea of Riobamba. The objective is to rescue several popular and traditional games that are no longer practiced pretty often. In order to the develop the study, a methodology with a quantitative and qualitative approach is applied since it integrates statistical numerical data and qualities of the games. The type of research is exploratory and Quasi-experimental. To obtain relevant information and comply with each of the objectives, a survey is applied, which contains 15 questions on the subject, the survey results show that currently students no longer play certain traditional games, they prefer to devote their free time to sedentary activities related to the use of internet, video games and television. Considering all these aspects, a guide of traditional games is proposed, detailing several activities that allow students to get out of their comfort zone and take advantage of their free time, contributing to improve physical and mental health and above all to prevent certain diseases. Finally, it is concluded that it is necessary the diffusion of traditional games in the institution taking into account the adequacy of certain spaces that generate a welfare to the students, it is recommended a progressive introduction of traditional games in the educational space of the students, the execution of the guide and the socialization with all the personnel that is part of the institution.